Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1038/nchembio.204
|View full text |Cite|
|
Sign up to set email alerts
|

A 21st century revisionist's view at a turning point in enzymology

Abstract: Despite the fact that the number of publications associated with the keyword 'enzyme' increases every year, the precise origin of enzyme catalysis has remained unresolved. Because of sustained intensive research efforts from an increasing number of laboratories, detailed information regarding the physics, chemistry and kinetics of enzymes is accumulating rapidly. The growing body of data contains many examples of kinetic behavior that are incompatible with a static view of enzyme catalysis. As a result, numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
413
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(426 citation statements)
references
References 64 publications
5
413
2
1
Order By: Relevance
“…In many cases it is clearly suggested that improving such effects will be crucial for optimal enzyme design (e.g., ref. 30). However, it seems to us that by far the main factor that actually contributes to catalysis is the preorganization effect and thus we feel that there is no rational way for improving dynamics and related effects as these factors do not contribute to catalysis (29).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases it is clearly suggested that improving such effects will be crucial for optimal enzyme design (e.g., ref. 30). However, it seems to us that by far the main factor that actually contributes to catalysis is the preorganization effect and thus we feel that there is no rational way for improving dynamics and related effects as these factors do not contribute to catalysis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of this include Ref. 158, that not only renamed the preorganization concept to describe something fundamentally different, but even more dangerously, incorrectly used the terminology of the original preorganization concept in doing this (see discussion in Ref. 2).…”
Section: Preorganization Is the Key Factor In Enzyme Catalysismentioning
confidence: 99%
“…It has been suggested that "promoting protein motions", i.e., specific fluctuations that might reduce the barrier height or promote tunneling by reducing donor-acceptor distances, can drive enzymatic reactions (1,2). Such models include promoting vibrations (3), environmentally coupled tunneling (1), and vibrationally enhanced ground-state tunneling (4).…”
mentioning
confidence: 99%
“…It has been suggested that "promoting protein motions", i.e., specific fluctuations that might reduce the barrier height or promote tunneling by reducing donor-acceptor distances, can drive enzymatic reactions (1,2). Such models include promoting vibrations (3), environmentally coupled tunneling (1), and vibrationally enhanced ground-state tunneling (4). Several of these proposals suggest that the anomalous temperature and pressure dependences of experimentally observed reaction rates and kinetic isotope effects are the consequence of protein motions on the pico-to femtosecond timescale that reduce the width and/ or height of the potential energy barrier along the chemical reaction coordinate.…”
mentioning
confidence: 99%